LITERTURE REVIEW : Efektifitas Metode Profile Matching Sebagai Pendukung Keputusan dalam Penilaian Kinerja Pegawai - Dennis Nugroho; Ida Rindaningsih (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
Quality human resources will support the success of a company or institution in achieving the goals that have been set. Ineffective human resource management, it is necessary to evaluate employee performance in order to know the condition of employee performance. In addition, performance appraisal can be used to determine awards, compensation, promotion, training, and career planning. The profile matching method is a decision support method by assuming that there is an ideal variable that must be owned. In other words, this method compares the expected profile competencies with the performance results achieved. The method used in this research is a literature review. The results of this study can be seen that the Profile Matching method is an effective, objective, fast, and accurate decision support system for use in performance appraisal. However, there are other opinions that state that the Profile Matching method is not suitable for use as a decision support system in the case of the best candidate.